Pengaruh Risk Profile, Good Corporate Governance, Corporate Social Responsibility terhadap Return Saham pada Perusahaan Perbankan Unit Usaha Syari’ah - Wijaya, Estu (Jurnal Pendidikan Indonesia, 2025)
The purpose of this study was to determine the effect of Risk Profile, Good Corporate Governance, and Corporate Social Responsibility on Stock Return. In banking companies in the Sharia Business Unit listed on the IDX. This study uses quantitative methods. The sampling technique used is purposive sampling. The results showed that the risk profile variable simultaneously had a positive and significant effect on stock returns . This is indicated by the F-statistic (9.702102 > 2.90) with a significance value of <a Prob. (0.0000 < 0.05). Partially, the Risk Profile variable has an effect on Stock Return, this is indicated by t-statistic > t-table (5.832663> 1.72913) with prob < a ( 0.0000 < 0.05). The size of the board of commissioners has no effect on stock returns, this is indicated by the t-statistic < t-table (-1.009617 < 1.72913) and the prob>a value (0.3254 > 0.05). The proportion of independent commissioners has no effect on stock returns. this is indicated by t-statistic <t-table (0.984251< 1.72913) and the value of Prob > a ( 0.3374 > 0.05). Corporate social responsibility has no effect on stock returns this is in match with t-statistics < t-table Corporate social responsibility (1.148739 < 1.72913) and the value of Prob. (0.2649 > 0.05).